THE LATE ROMAN EMPIRE IN THE REFLECTION OF DOMESTIC HISTORIOGRAPHY (XIX - FIRST HALF OF THE XX CENTURIES) - Evgeniya Zaytseva; Artem Skvortsov (Гуманитарные и юридические исследования)
The article considers the interpretation of the Late Roman empire by pre-revolutionary and Soviet researchers. The subject attracted special interest in the antiquity rarely. Nevertheless it was covered in some detail, especially in the pre-revolutionary period. Despite the fact that the period of the Late Roman Empire became the object of careful attention of scientists, work that covered all spheres of the late-antique society was not created. However many aspects of the life of the society of the end of the III-V centuries were covered in pre-revolutionary historiography as a whole. Soviet historians continued the socio-economic direction in the study of the history of the Late Roman Empire, attempting to include it in the last stage of the "slave revolution". The period of late antiquity (III-V centuries) was assigned a decisive role in this theory, since the social struggle was to be exacerbated precisely during this period. The political aspect of the dominant was interpreted by domestic historiographers as an absolute military-bureaucratic monarchy, which began to take shape even during the Principate period, and finally took shape in the fourth century.